2020
DOI: 10.21203/rs.3.rs-31134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of multiple SARS-CoV-2 proteins by an antiviral biomolecule, seselin from Aegle marmelos deciphered using molecular docking analysis

Abstract: Our earlier experimental and computational report produced the evidence on anti-viral nature of the compound seselin purified from the leaf extracts of Aegle marmelos against Bombyx mori Nuclear Polyhedrosis Virus (BmNPV). In the pandemic situation of COVID-19 caused by SARS-COV-2 virus, an in silico effort to evaluate the potentiality of the seselin has been made to test its efficacy against multiple targets of SARS-COV-2 such as SARS-CoV-2S spike protein, COVID-19 main protease and free enzyme of the SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This plant produces a bioactive compound named seselin having activity against multiple targets of SARS-CoV-2. In silico molecular docking study showed that seselin has inhibitory potential to the receptors SARS-CoV-2S protein (binding energy: 6.6 kcal/mol), COVID-19 main protease (−6.9 kcal/mol), and free enzyme of the SARS-CoV-2 (2019-nCoV) main protease (−6.7 kcal/mol) ( Nivetha et al, 2021 ).…”
Section: Antiviral Plants Of Bangladeshmentioning
confidence: 99%
“…This plant produces a bioactive compound named seselin having activity against multiple targets of SARS-CoV-2. In silico molecular docking study showed that seselin has inhibitory potential to the receptors SARS-CoV-2S protein (binding energy: 6.6 kcal/mol), COVID-19 main protease (−6.9 kcal/mol), and free enzyme of the SARS-CoV-2 (2019-nCoV) main protease (−6.7 kcal/mol) ( Nivetha et al, 2021 ).…”
Section: Antiviral Plants Of Bangladeshmentioning
confidence: 99%
“…The potential activity of curcumin against SARS-CoV-2 has been demonstrated by (14), using the molecular docking method to determine the affinity of binding between the active molecule and COVID-19 proteases[A12] 15,16 . 6LU7 AND 6Y2E expressed in kcal/mol obtain favorable results and recommend the plant species for future studies[A13] [17][18][19] . Due to its various properties, curcumin has the potential for the development of new drugs 4 .…”
Section: Background Medicinal Plants Speciesmentioning
confidence: 99%
“… 60 Seselin showed efficacy against multiple targets of SARS-COV-2 such as spike protein and M pro . 61 However, evidence of these compounds for the treatment of COVID-19 is lacking. Therefore, these compounds were studied for their inhibitory action against SARS-CoV-2 RdRp.…”
Section: Introductionmentioning
confidence: 99%